A STUDY OF THE UTILIZATION OF COUGH SYRUPS CONTAINING CODEINE AMONG DRUG ABUSERS IN ASKIRA UBA LOCAL GOVERNMENT AREA OF BORNO STATE NIGERIA - Uthman GS; Danjuma CU; Usama UB; Jidda MS (Ntec Specialist, 2016)
Background: The Directorate of Narcotic and Controlled substances of the National Agency for Food and Drug Administration and control (NAFDAC) disclosed that a large number of Nigerians are abusing prescription of codeine. Objective: The following work study the illicit use of cough syrup within Askira Uba Local Government Area of Borno State of Nigeria, with the aim of understanding the sociodemographic factors surrounding the phenomenon within the study community. Methods: A questionnaire based survey was conducted within the study area. Volunteers numbering 83 were recruited from pharmaceutical premises that consented to participate in the study within the Local Government Area. The questionnaire basically addressed the sociodemographic characteristics of users of cough syrups containing codeine (CCCS) and other circumstances surrounding the usage. Data obtained were analysed using simple descriptive statistics. Results: Most of the volunteers recruited turned out to be males (n= 73, 90.1%), aged between 20 to 30 years (n=51, 63.0 %) with substantial proportion having senior secondary school certificates as the highest educational attainment (n= 26, 32.2 %). Most respondents uses 1 to 3 bottles per day (n=77, 95.1%). Feeling of euphoria appeared to be the most popular goal of abusing CCCS (n=31, 38.3%) despite the weaknesses and discomfort that always followed a session or its absence. Conclusion: CCCS use in Askira Uba is essentially a youthful male problem that appears to be a consequence of search for happiness and excitement